Pengaruh Struktur Modal, Pertumbuhan Laba, Investment Opportunity Set dan Hutang Lancar terhadap Profitabilitas pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Sherine Christy Wijaya; Vania Wang; Hot Rikardo Marpaung; Nina Purnasari (SOSEK : Jurnal Sosial dan Ekonomi, 2021)
Manufacturing companies have a important rule in our economic, with the growing of a company in the manufacturing sector signaling economic growth in Indonesia. This research aims to test the Effect of Capital Structure, Profit Growth, Investment Opportunity Set and Short Term Liabilities Toward Profitability in Manufacturing Companies Listed in Indonesia Stock Exchange. Quantitative approach method is data that are nominal figures from financial statements or summary financial statements taken from Indonesia Stock Exchange. The population of this research is 177 manufacturing companies listed on the Indonesian Stock Exchange Period 2016-2019. The samples have 276 companies. Multiple linear regression test. The research result is the Capital Structure has no partial effect toward profitability in manufacturing companies listed in Indonesia Stock Exchange. Profit growth has no partial effect toward profitability in manufacturing companies listed in Indonesian Stock Exchange. Investment Opportunity Set has no partial effect toward profitability in manufacturing companies listed in Indonesia Stock Exchange. Short Term Liabilities has no partial effect toward profitability in manufacturing companies listed in Indonesia Stock Exchange. Capital Structure, Profit Growth, Investment Opportunity Set and Short Term Liabilities has a simultaneous effect toward profitability in manufacturing companies listed in Indonesian Stock Exchange.